Defining a COPD composite safety endpoint for demonstrating efficacy in clinical trials: results from the randomized, placebo-controlled UPLIFT® trial. Issue 1 (December 2016) - Celli, Bartolomé; Decramer, Marc; Liu, Dacheng; Metzdorf, Norbert; Asijee, Guus; Tashkin, Donald
Abstract Background Chronic obstructive pulmonary disease (COPD) clinical trials evaluating hard endpoints (mortality, hospitalized exacerbations) require a large number of subjects and prolonged observational periods. We hypothesized that a composite endpoint of respiratory outcomes (CERO) can help evaluate safety and benefit in COPD trials. Methods Retrospective analysis of 5992 patients enrolled in the 4-year UPLIFT® trial, a randomized trial of tiotropium versus placebo in patients with moderate-to-severe COPD. Patients were permitted to continue using their usual COPD medications except for other anticholinergics. The CERO included deaths, respiratory failure, hospitalized exacerbations, and trial dropout due to COPD worsening. The incidence rates (IRs) per 100 patient-years and risk ratios (RRs and 95 % CI) were determined at years 1 to 4. The effect of treatments on CERO was similarly assessed. A power analysis helped calculate the sample size needed to achieve outcome differences between treatments. Results The CERO IRs at years 1 to 4 for tiotropium versus placebo were 16, 13, 11, and 11, and 21, 16, 14, and 13, respectively. The RRs of CERO between tiotropium and placebo at the same time points were: RR-year 0.76 (0.67, 0.86), 0.80 (0.72, 0.88), 0.81 (0.74, 0.89), and 0.84 (0.77, 0.92). Using the IRs and RRs, the sample size (alpha = 0.05 two-sided, 90 % power) for studies of 1, 2, 3, and 4 years would be 1546, 1392, 1216, and 1504 per treatment group, respectively, with 575, 810, 930, 1383 required events, respectively, for hypothetical, event-driven studies. Conclusions A composite endpoint incorporating relatively infrequent serious or significant COPD-related safety outcomes could be useful in clinical trials. In UPLIFT®, CERO events were significantly reduced in patients receiving tiotropium compared with placebo. Trial registration NCT00144339 .